2003
DOI: 10.1002/jbm.a.10584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strain and strain rate on fatigue‐accelerated biodegradation of polyurethane

Abstract: A diaphragm-type film specimen was used to study in vitro degradation of poly(etherurethane urea) (PEUU) under conditions of dynamic loading. This geometry allowed both uniaxial and biaxial loading in a single experiment. During testing, the film was exposed to a H(2)O(2)/CoCl(2) solution that simulated in vivo oxidation of PEUU. The combination of dynamic loading and biaxial tensile strain accelerated oxidative degradation. The effects of biaxial strain magnitude and strain rate were examined separately by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
(62 reference statements)
1
22
0
Order By: Relevance
“…Furthermore, the applied strain itself, in the absence of a chemically reactive environment, did not change the mechanical properties of the suture. With polyurethane (on which the degradation mechanism is oxidation), Wiggins et al (Wiggins et al 2003) found that the degradation rate of polyurethane increased with increasing cyclic strain rate, while the magnitude of the strain magnitude had essentially no effect. Their experiments employed a circular membrane device in which pressure was applied to one side of the membrane, causing it to deflect into a well.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the applied strain itself, in the absence of a chemically reactive environment, did not change the mechanical properties of the suture. With polyurethane (on which the degradation mechanism is oxidation), Wiggins et al (Wiggins et al 2003) found that the degradation rate of polyurethane increased with increasing cyclic strain rate, while the magnitude of the strain magnitude had essentially no effect. Their experiments employed a circular membrane device in which pressure was applied to one side of the membrane, causing it to deflect into a well.…”
Section: Introductionmentioning
confidence: 99%
“…This is 303 adequately covered in literature (Stokes et al, 1995;Wiggins et al, 2003;Thoma, 1987;Schmidt et 304 al., 1998;Zhao et al, 1990Zhao et al, , 1991Wu et al, 1992;Schubert et al, 1995Schubert et al, , 1997 …”
mentioning
confidence: 98%
“…Their superior mechanical properties and 10 blood compatibility has favored their use and development as biomaterials, particularly as 11 components of implanted devices (Lamba et al, 1997). Polyurethane elastomers offer superior 12 mechanical properties over silicone elastomers, particularly in relation to tear and abrasion, and flex-13 fatigue life (Wiggins et al, 2003). The chemical composition of these elastomers offers substantial 14 opportunities to synthetic polymer chemists to tailor the structures to meet specific requirements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wiggins et al 78 found that the degradation rate of polyurethane increased with increasing cyclic strain rate, whereas strain magnitude had essentially no effect. Their experiments employed a circular membrane device in which vacuum was applied to one side of the membrane, causing it to deflect into a well.…”
Section: Polymer Degradation Under Unloaded and Loaded Conditionsmentioning
confidence: 97%